Answer:
y = -1
+ 1
Explanation:
The line (a) passing through point (3, -4) is perpendicular to line (b) whose equation is; y = -2 +
x
The slope of line (b) =
![(3)/(5)](https://img.qammunity.org/2020/formulas/mathematics/high-school/ham59d8d32yipgtxeagz7evpc6d3yqvvcb.png)
For perpendicular lines, the product of their slopes = -1
So line (a) has a slope of: -1 ÷
= -
![(5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/932m3fox3fmk5lfk3tls2eyev0gf4uzdnd.png)
Taking another point (x,y) on line (a);
Slope = change in y ÷ change in x
= -
![(5)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/932m3fox3fmk5lfk3tls2eyev0gf4uzdnd.png)
y + 4 =
(x - 3)
y = -
x + 5 - 4
y = -
x + 1
Finally,
y = -1
+ 1